WORKSHOP DESAIN BROSUR SEKOLAH SMK MAHARDIKA BERBASIS BITMAP - Setyorini Setyorini; Jaenal Arifin; Nicholaus Wayong Kabelen (IKIP PGRI Bojonegoro, 2017)
Training is a process of helping students to get soft skills to prepare for the future world of work through the development of skills, thoughts, actions, knowledge and good attitude. SMK Mahardika is a vocational school that has the purpose to create students who are ready to work with a given skills that match the needs in their work place. Designing brochure is one of the additional skills students can have to show their ability that can be utilized in the workplace. One of the skills designing that they can make brochures, banners, posters and stickers by using object images formed based on point and color combination (Graphic Bitmap). Community Service Commitment is one part of Tri Darma Perguruan Tinggi which must be implemented by the academic community, especially the lecturers. In this period the title of the workship is